2017
DOI: 10.18203/2320-1770.ijrcog20170373
|View full text |Cite
|
Sign up to set email alerts
|

Active management of third stage of labour with low doses of oral misoprostol and oxytocin on low: risk parturient in a Sub-Saharan hospital, Dakar, Sénégal

Abstract: Background: Assess the effectiveness of oral misoprostol as an alternative to oxytocin in the active management of the third stage of labour in Dakar/Senegal.Methods: Randomized controlled clinical trial conducted in the maternity ward of a university hospital on 304 women who had vaginal delivery. These women were randomly assigned into 2 groups based on active delivery conditions: the first group received an oral administration of misoprostol (400 mcg) and the second group 5 IU oxytocin through intravenous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Studies from other underdeveloped and developing countries report similar findings [14,15], despite showing the higher amount of blood loss, the need for additional uterotonics, and the adverse effects in the misoprostol group. They have mainly focused on statistical differences in a smaller sample size scenario.…”
Section: Discussionmentioning
confidence: 58%
“…Studies from other underdeveloped and developing countries report similar findings [14,15], despite showing the higher amount of blood loss, the need for additional uterotonics, and the adverse effects in the misoprostol group. They have mainly focused on statistical differences in a smaller sample size scenario.…”
Section: Discussionmentioning
confidence: 58%
“…The frequency of side effects was also significantly higher in the misoprostol group than in the oxytocin group. Studies in other underdeveloped and developing countries have reported similar results [22,23] but the misoprostol group showed greater blood loss, the need for additional uterotonics, and side effects has been done. They mainly focused on statistical differences in small sample size scenarios.…”
Section: Discussionmentioning
confidence: 84%
“…The efficacy of misoprostol alone as well as an adjunct to oxytocin for prevention of PPH is well documented. [9][10][11][12][13][14][15][16][17][18][19][20] In contrast very few studies have reported a contrary view but have used a lower dose. 21 Choosing the optimal dose is imperative to achieve the goal as discussed later.…”
Section: Discussionmentioning
confidence: 99%